YOUTH LANGUAGE AND ITS ROLE IN MODERN SOCIETY - Jumanazarova Mahliyo Ulugʻbekovna; Zoyirova Dilfuza Xayriddinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In the dynamic landscape of modern society, youth language plays a crucial role in shaping cultural identities, social interactions, and communication practices. This informal and often evolving language, composed of slang, abbreviations, and code-switching, reflects the attitudes, experiences, and values of younger generations. As new technological platforms and global cultural exchanges continue to influence how young people communicate, the role of youth language in society becomes more significant.